PEMBELAJARAN KETERAMPILAN BERBICARA DALAM PENGGUNAAN SOR SINGGIH BAHASA BALI - Pande Putu Pawitra Adnyana (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
Balinese language is the mother tongue of Balinese. This language is used in the daily life of Balinese. It is also a historical evidence for Balinese that takes a position as a means of expression in Balinese culture, in which inside it, it has recorded, such as aesthetic experience, religion, social, politics and other aspects of Balinese life. In its development, there are some levels in Balinese language appeared and they are called sor singgih of Balinese Language. The problem discussed in this study include (1) the process of learning sor singgih of Balinese language in the speaking skil, (2) the mastery of sor singgih of Balinese language in the speaking skill, (3) factors that affects students' performance in mastering it. The data were collected by doing an analysis upon conversation conducted by students. The data were selected and analyzed in descriptive and qualitative ways. Based on the analysis, there were weakness and lack of learning aids used and also some errors found in students' performance while using sor singgih of Balinese language due to the influence of Indonesian, the characteristic of students, along side with facilities and basic facilities as the supporting factors of the affectivity of speaking.